Deutscher Burschentag 1924 in Danzig - Urban, Hans (1874-?). (Danizg : [wydawca nieznany], 1924)
Karta pocztowa z panoramą Gdańska.
Keywords: Studenci -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- karty pocztowe